HOW DO GEN Z MUSLIM CONSUMERS DECIDE TO PURCHASE UMAMA SCARF HIJABS ONLINE? - Sayuti, Vina Nur Anis; Subagio, N. Ari; Amijaya, Rachmania Nurul Fitri (Universitas Airlangga, 2025)
The large number of Muslim populations in Indonesia provides a large consumer potential for the business world. This can be seen from the many businesses that are now trying to meet consumer needs for sharia products and services, one of which is wearing the hijab. The purpose of this study was to analyze the significant influence of electronic word of mouth, influencer marketing, sales promotion and price on the purchasing decisions of generation Z Muslim consumers on the Umama Scarf hijab product. The sampling technique in this study used purposive sampling. The population in this study were generation Z Muslim consumers in Jember Regency who had made online purchases of the Umama Scarf hijab product twice. This study used multiple linear regression analysis methods. The results showed that the variables electronic word of mouth, influencer marketing, sales promotion and price had a significant effect on increasing purchasing decisions. This shows that generation Z pays attention to the intensity, content, and reviews of consumers who have purchased the Umama scarf hijab online. Purchasing decisions are influenced by the needs factor felt by generation Z in terms of decisions and how consumers experience information about the Umama Scarf hijab product from influencers. By offering discounts, free coupons to create better prices to increase purchasing decisions.